The Effect of Picture Series on Students’ Narrative Writing at Course and English Club Kampoeng Pare Mataram - Saputra, Indra Atriyana; Ilham, Ilham; Asbah, Asbah (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to investigate the effect of using Picture Series on the narrative writing skills of EFL learners at CEC Kampoeng Pare Mataram. It employed a pre-experimental one-group pretest–posttest design involving fifteen junior high school students. Students’ writing ability was measured using a narrative writing test assessed through an analytic scoring rubric adapted from Brown (2007), covering content, organization, vocabulary, language use, and mechanics. The results showed a significant improvement in students’ writing performance, with mean scores increasing from 56.73 to 75.67. A paired sample t-test confirmed that the improvement was statistically significant (p 0.05). These findings indicate that Picture Series effectively enhances idea development and narrative coherence. Therefore, this study provides empirical support for the use of Picture Series as an effective medium in teaching narrative writing in EFL contexts, particularly in non-formal educational settings.